2016
DOI: 10.1016/j.seizure.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Increased resting-state EEG functional connectivity in benign childhood epilepsy with centro-temporal spikes

Abstract: Areas of increased EEGfC topographically correspond to cortical areas that, based on relevant literature, are related to speech and attention deficit in BECTS children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…An additional limitation is that IEDs appear to significantly affect functional connectivity measurements. Nearly all studies accounting for the presence of IEDs have observed a relationship between the IEDs and connectivity patterns . Similarly, graph theory analyses also suggest widespread effects of IEDs .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…An additional limitation is that IEDs appear to significantly affect functional connectivity measurements. Nearly all studies accounting for the presence of IEDs have observed a relationship between the IEDs and connectivity patterns . Similarly, graph theory analyses also suggest widespread effects of IEDs .…”
Section: Discussionmentioning
confidence: 94%
“…Nearly all studies accounting for the presence of IEDs have observed a relationship between the IEDs and connectivity patterns. 13,48,49,52,54,[61][62][63] Similarly, graph theory analyses also suggest widespread effects of IEDs. 94 Brief alterations in neurophysiological signals, including both blood oxygen level-dependent contrast imaging and electromagnetic measurements, will inherently change the time-course correlations between affected and remote brain regions.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Of the wide variety of imaging modalities used for functional connectivity, scalp electroencephalogram (EEG) is desirable due to its accessibility, low cost, standardized clinical application, noninvasive nature, and high temporal resolution. EEG-based FCNs have been used to characterize pathological networks associated with temporal lobe epilepsy (Quraan et al 2013), benign epilepsy with centrotemporal spikes (Clemens et al 2016;Mahmoudzadeh et al 2016), and generalized pharmacoresistant epilepsies (Horstmann et al 2010). When these FCNs are based on cross-correlation or coherence techniques using at least 100 seconds of EEG data, the networks exhibit stability over time, making them suitable for assessing an underlying disease state (Chu-Shore et al 2012).…”
Section: Introductionmentioning
confidence: 99%